2019
DOI: 10.1177/1179573519843872
|View full text |Cite
|
Sign up to set email alerts
|

A Collaborative Approach: Care Staff and Families Working Together to Safeguard the Quality of Life of Residents Living With Advanced Dementia

Abstract: Objectives: This study aimed to explore the quality of life and well-being of care home residents living with advanced dementia, how personalised care can be achieved where the person is completely dependent on others for care and how individuals’ choices and human rights were upheld. Methods: The study design used a qualitative approach, with data collected through in-depth, semi-structured interviews with 8 family members, all of whom visited daily, and 8 care staff. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In dementia care, informal caregivers act as person-centred information sources ( Ponnala, Block, Lingg, Kind, & Werner, 2020 ), advocators ( Bunn et al, 2017 ) and decision-makers ( Livingston et al, 2010 ), which is especially important to provide person-centred ( Reid & Chappell, 2017 ) due to the cognitive decline and communication difficulties of persons with dementia ( Hinton et al, 2007 ). Moreover, through expressing the personal wishes and needs of the persons with dementia, informal caregivers contribute to ensuring comfort, enjoyment and satisfaction ( Fox et al, 2018 ), and support healthcare professionals in understanding distressed behaviours of persons with dementia ( Hughes et al, 2019 ). We have described in our findings that by sharing personal information and needs, family members may prevent escalations due to challenging behaviours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In dementia care, informal caregivers act as person-centred information sources ( Ponnala, Block, Lingg, Kind, & Werner, 2020 ), advocators ( Bunn et al, 2017 ) and decision-makers ( Livingston et al, 2010 ), which is especially important to provide person-centred ( Reid & Chappell, 2017 ) due to the cognitive decline and communication difficulties of persons with dementia ( Hinton et al, 2007 ). Moreover, through expressing the personal wishes and needs of the persons with dementia, informal caregivers contribute to ensuring comfort, enjoyment and satisfaction ( Fox et al, 2018 ), and support healthcare professionals in understanding distressed behaviours of persons with dementia ( Hughes et al, 2019 ). We have described in our findings that by sharing personal information and needs, family members may prevent escalations due to challenging behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored interprofessional collaboration between informal caregivers of persons with dementia and healthcare professionals in home care (HC), in nursing homes and during nursing home transitions. These studies mainly showed that informal caregivers act as caregivers ( White et al, 2018 ); provide person-centred information to stimulate tailored dementia care ( Häikiö, Sagbakken, & Rugkåsa, 2020 ); make decisions regarding assessments and care plans ( Dalgarno et al, 2021 ; Hughes, Woods, Algar-Skaife, Jelley, & Jones, 2019 ); facilitate continuity and management of care ( Bunn et al, 2017 ); and contribute to the overall quality of life ( Hughes et al, 2019 ) of persons with dementia in HC. Furthermore, in nursing homes, interprofessional collaboration between informal caregivers and nursing home staff is important as well due to their continued involvement in ( Backhaus et al, 2020 ), for example, providing personal care ( Häikiö et al, 2020 ; Roberts & Ishler, 2017 ); watching over the care process ( Hoek et al, 2020 ); providing psychosocial support ( Gaugler, 2005 ); and providing support in solving problems ( Jang, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of relatives' involvement in issues of resident dignity, integrity or well-being stress the necessity for staff to build trust and relationships with relatives to ensure that the resident's voice is considered [41][42][43][44][45]. In a Dutch study of end-of-life care in 34 NH, 252 family members reported unpleasant experiences such as neglect and lack of respect for the patient [46].…”
Section: Residents and Relatives In Nhmentioning
confidence: 99%
“…A key finding in a recent qualitative study of relatives and care staff collaboration was that staff and relatives together were able to identify factors of residents' well-being, and family members who visited daily worked collaboratively with care staff to maintain the quality of life of their relatives and engaged in proxy decision-making. The result was that they managed to avoid abuse [45]. Including the relatives in a symmetrical collaboration on the relative's own terms is therefore of utmost importance.…”
Section: Maltreatment Of Relatives To Nh Residentsmentioning
confidence: 99%
“…Moreover, taking into account individual experiences of people with MNCD, it is necessary to understand their unmet needs during the different stages of diseases, and it is mandatory to discuss how to increase and to support their quality of life and how to sustain their autonomy and independence [ 21 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. There is still an open debate on the need to support people with MNCD in living in their homes and in their environments and, when they choose to live in medium and long-term facilities, it is important to support them also in this experience [ 51 , 52 , 53 , 54 ].…”
mentioning
confidence: 99%